THE COMPARISON OF MONOTHERAPIES OF KELOID SCARS BY LASER, SILICONE GEL, 5-FLUOROURACIL AND CRYOTHERAPY TREATMENTS - A LITERATURE REVIEW - Zięba, Anita; Domin, Michał; Kowalska, Monika; Ścibisz, Katarzyna; Całka, Justyna; Zdobylak, Dominika; Ollik, Karolina; Harenza, Kamil; Taranowicz, Mateusz; Kowalczyk, Olga (International Journal of Innovative Technologies in Social Science, 2026)
Keloid scars are a common problem of abnormal wound healing. There are plenty of treatment options. There is why, in this review 4 of them (laser, silicone gel, 5-fluorouracil and cryotherapy) were examined separately as monotherapies and compared. The aim of the review was to find out whether there could be found an effective monotherapy of keloids and which one of the examined ones could be the most promising one. In the review there were 28 studies analyzed focused on laser, silicone gel, 5-fluorouracil and intralesional cryotherapy as monotherapies of keloids. They included some randomized controlled trials, systematic reviews, observational studies and in vitro investigations. All the literature based on combined therapies was excluded. The effectiveness, safety and rate of recurrence was assessed. All of the therapies showed some improvements in the appearance of scars and the symptoms. However, the quality of evidence was low due to limitations of the studies and lack of long-term outcomes. Intralesional cryotherapy seems to bring the most promising results but equally the highest risk of side effects. The other 3 methods had very similar results. None of the proposed treatments can be defined as an effective monotherapy of keloid scars. There is a high need of conducting more research focused on standardized procedures with big randomized groups of patients and the follow-ups to examine long-term recurrence rate. It could be also suggested that monotherapy may not be the best way of treatment and the further research should be focused on combined therapies.